2014
DOI: 10.2224/sbp.2014.42.2.177
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Savoring in Work-Family Conflict

Abstract: Building on positive psychology research, I examined savoring as an important positive psychological asset of the individual, and investigated its impact on work-family conflict (WFC). Data were gathered from 354 dual-earner couples working in different organizations. Hierarchical regression analyses revealed that savoring was negatively related to WFC, indicating that individuals who are high in the capacity for overall savoring, experience lower levels of work-family conflict than do those low in that capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…A deferred impact of the intervention was highlighted in the intervention group, from pretest to the 4‐week follow‐up for dyadic adjustment and quality of the interaction. This maintenance is in line with that of another type of activity encompassed by the CPPI, encouraging sharing, savouring, and capitalizing, which invited participants to appreciate shared activities (i.e., create and schedule positive moments with my partner and how to respond in an active and constructive way to my partner; Bryant, Chadwick, & Kluwe, ; Camgoz, ; Gable, Gonzaga, & Strachman, ; Quoidbach, Berry, Hansenne, & Mikolajczak, ). These CPPI activities aimed to expand the participants' focus on all aspects of their ongoing romantic relationship and to increase their positive interactions (Kauffman & Silberman, ).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A deferred impact of the intervention was highlighted in the intervention group, from pretest to the 4‐week follow‐up for dyadic adjustment and quality of the interaction. This maintenance is in line with that of another type of activity encompassed by the CPPI, encouraging sharing, savouring, and capitalizing, which invited participants to appreciate shared activities (i.e., create and schedule positive moments with my partner and how to respond in an active and constructive way to my partner; Bryant, Chadwick, & Kluwe, ; Camgoz, ; Gable, Gonzaga, & Strachman, ; Quoidbach, Berry, Hansenne, & Mikolajczak, ). These CPPI activities aimed to expand the participants' focus on all aspects of their ongoing romantic relationship and to increase their positive interactions (Kauffman & Silberman, ).…”
Section: Discussionsupporting
confidence: 71%
“…In the current study, couples in the intervention group showed improvements in dyadic variables (i.e., quality of interaction and dyadic adjustment) and in mutuality communication patterns over the course of the intervention compared with those in the control condition. Such observations are in line with the fact that social sharing of emotions between romantic partners, involving savouring and capitalization processes, may improve positive interactions within the couple (Camgoz, ; Gable & Reis, ). Moreover, the addition of a short weekly mindfulness practice might have added another tool to foster communication improvement (Atkinson, ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Shimazu [10] shows that work or workaholism among women can cause job-family conflict more than that among men. On the other hand, the results of some studies conducted in this field indicate that job-family conflict is associated with a wide range of negative consequences, such as a decrease in marital satisfaction and life moment enjoyment [11,12]. Sexual satisfaction refers to the couple's perception of sex life.…”
Section: Introductionmentioning
confidence: 99%
“…Savoring is associated with but different from happiness and pleasure (Camgoz, 2014). It refers to the active ISSN 1648-3898 process of enjoyment that involves "a higher order awareness or reflective discernment on the part of the individual" (Bryant & Veroff, 2007).…”
Section: Introductionmentioning
confidence: 99%